Humanitarian Conflict in Myanmar from the Perspective of International Law and Human Rights - Habibi, Muhammad Badri; Taufiqi, Muchammad Zidan (Peradaban Journal of Law and Society, 2023)
This article presents an analysis of the humanitarian conflict in Myanmar from the perspective of international law and human rights. The study employs a normative legal approach, focusing on legislation, case studies, and analytical methods. Through this research, we gain an understanding of the relevant international legal framework and norms pertaining to the protection of human rights in the context of the conflict in Myanmar. Case studies on human rights violations are utilized to examine international legal responses and efforts to ensure accountability. The article emphasizes the importance of protecting and upholding human rights in addressing the humanitarian conflict in Myanmar. It is hoped that this contribution will expand understanding of the significance of international law and human rights in achieving sustainable justice and peace in Myanmar and globally.